A systematic literature review informing library and information professionals' emerging roles. Issue 1 (12th January 2015) - Vassilakaki, Evgenia; Moniarou-Papaconstantinou, Valentini
Abstract : Purpose: – This paper aims to provide a systematic review of the specific roles information professionals have adopted in the past 14 years. It aims to identify the roles reported in the literature concerning developments in the Library and Information Science (LIS) profession. Design/methodology/approach: – This study adopted the method of systematic review. Searches were conducted in February and March 2014 on different LIS databases. From a total of 600 papers, 114 were selected, based on specific inclusion and exclusion criteria. A thorough full-text analysis of the papers revealed six roles that librarians have adopted: teachers, technology specialists, embedded librarians, information consultants, knowledge managers and subject librarians. Findings: – New and evolving roles were identified, mainly in the context of academic libraries. Librarians' educational responsibilities and their active involvement in the learning and research process were highlighted in all role categories identified. Collaboration among faculty and librarians was reported as a way of ensuring successful instruction. Librarians' personal views of their new and emerging roles were more frequently reported; further research is needed to shed light on academics, students and other users' perceptions of librarians' engagement in the learning process. Research limitations: – The study considered only peer-reviewed papers published between 2000 and 2014 in English. It focused on information professionals' roles and not on librarians' skills and their changing professional responsibilities. Originality/value: – This review paper considers the development of the LIS profession in a changing environment and offers an understanding of the future direction of the LIS profession.